2017
DOI: 10.2147/oajsm.s133811
|View full text |Cite
|
Sign up to set email alerts
|

Injuries and illnesses in a cohort of elite youth alpine ski racers and the influence of biological maturity and relative age: a two-season prospective study

Abstract: BackgroundStudies on injuries and illnesses involving youth ski racers younger than 15 years are lacking in the literature. The aim of this study was prospectively to assess the incidence, prevalence, and severity of traumatic and overuse injuries, as well as illnesses of elite youth ski racers with regard to sex, biological maturity status, and relative age.Subjects and methodsA prospective, longitudinal cohort design was used to monitor the anthropometrics, training characteristics, traumatic and overuse inj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
56
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(67 citation statements)
references
References 36 publications
11
56
0
Order By: Relevance
“…While for younger athletes (ie, skiers before the growth spurt), no sex differences and relatively low absolute rates of acute injuries were reported (15.8 injuries per 100 athletes per winter season), 21 and two studies in elite athletes (ie, skiers after the growth spurt) revealed absolute injury rates of 36.7 and 36.2 injuries per 100 athletes per winter season 14,15 . Moreover, on the elite level males were found to have higher overall injury rates than females 14,15 .…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…While for younger athletes (ie, skiers before the growth spurt), no sex differences and relatively low absolute rates of acute injuries were reported (15.8 injuries per 100 athletes per winter season), 21 and two studies in elite athletes (ie, skiers after the growth spurt) revealed absolute injury rates of 36.7 and 36.2 injuries per 100 athletes per winter season 14,15 . Moreover, on the elite level males were found to have higher overall injury rates than females 14,15 .…”
Section: Discussionmentioning
confidence: 92%
“…However, to the best of our knowledge, there are only three epidemiological studies that focused on youth competitive alpine skiers yet. While in a skiing cohort with an average age of 11.7 years, the rates of acute and overuse injuries were still relatively low, 21 for skiers after growth spurt (16.7 years in average) injury risk revealed to be as high as at the elite level 18,19 . These observations may lead to the hypothesis that the growth spurt induces a first substantial increase in injury risk.…”
Section: Introductionmentioning
confidence: 93%
“…There is no knowledge available to substantiate whether injuries and burnout early in an athlete’s career will result in premature departure of sport. The relative age effect is an often discussed topic, favouring those athletes born early in a calendar year 64. There were different age classes across sports in BA YOG (online supplementary appendix 9), but these were more due to practical issues related to qualification events within each International Sports Federation to make up the final participants for BA.…”
Section: Discussionmentioning
confidence: 99%
“…Taller, heavier and early maturing athletes have performance and selection advantages in youth alpine ski racing [35,36] and are at a lower injury risk or less vulnerable for severe injuries [37]. The adolescent growth spurt leads to anthropometric changes, and therefore, affects coordinative abilities [38].…”
Section: Discussionmentioning
confidence: 99%